ANALISIS HUBUNGAN KETIDAKPASTIAN KEBIJAKAN MONETER THE FED TERHADAP PDB DEFLATOR INDONESIA : (ANALISIS HUBUNGAN KETIDAKPASTIAN KEBIJAKAN MONETER THE FED TERHADAP PDB DEFLATOR INDONESIA) - Sukma Falih, Daffa; Seno Aji, Tony (Jurnal Ekonomika : INDEPENDEN, 2025)
This research aims to determine the Fed’s monetary policy relationship as measured using the Monetary Policy Uncertainty (MPU) index, Consumer Price Index, Commodity Exports, and Exchange Rates on GDP on its Causality to Indonesia’s GDP Deflator. This research uses a quantitative approach with quarterly time series data from 2000 to 2023. The data is secondary from the Federal Reserve Economic Data (FRED). In addition, Granger Causality analysis was used to analyze the causality between variables. The results show that there is no bidirectional causality between variables. However, there is only unidirectional causality especially the MPU Index to the GDP Deflator and Export Commodity to the GDP Deflator.